THU0230 Is There A Difference in The Presentation of Male and Female Patients with Juvenile Systemic Sclerosis? Results from The Juvenile Scleroderma Inception Cohort. (15th July 2016) - Foeldvari, I.; Klotsche, J.; Kasapcopur, O.; Adrovic, A.; Terreri, M.T.; Stanevicha, V.; Katsikas, M.M.; Alexeeva, E.; Sztajnbok, F.; Cimaz, R.; Kostik, M.; Sifuentes-Giraldo, W.A.; et al.
Abstract : Background: Juvenile systemic sclerosis (jSSc) is an orphan autoimmune disease. Several adult publications looked at the differences between male and female patients with Systemic Sclerosis. There is rarity of data regarding this topic in pediatric jSSc. The juvenile scleroderma inception cohort (www.juvenilescleroderma.com ) is a prospective standardized register for patients with jSSc. Objectives: comparison of patients characteristic at the time of inclusion in the registry who are male or female. Methods: Patients with jSSc were included worldwide to the juvenile scleroderma inception cohort. We compered the demographics and clinical characteristics of the male and female patients. Results: Up till now 74 patients were enrolled, 54 with djSSc (76%) and 18 with ljSSc (24%). 14 (19%) of the patients were male (M) and 60 female (F) (81%). The mean disease duration at the time of inclusion was 9.3 in M and 9.2 in F patients. 74.4% of the M and 76.7% of the F had diffuse subset. The mean age of the onset of Raynaud symptomatic was 9.3 in M and 9.2 years in the F patients and the non-Raynaud symptomatic with 9.1 in M and 9.9 in F patients. At the time of the inclusion the mean modified Rodnan Skin Score was 20 in M and 15.1 in F patients. Anti-Scl 70 positivity was found in 42.9% in M and 32.1% in F patients. Anticentromere positivity occurred in 16.7% in M and 3.3% in F patients (p=0.027). Capillary changes were present in 50% of the M and 60% of F patients, but 50% in M and F had already history of ulcerations, but 28.6% in M and 15.5% in F had active ulceration. 57.1% of the M and 50% of the F patients had cardiopulmonary involvement. Six patients had pulmonary hypertension, they were all F. 75% of M and 46.7% of F patients had signs of interstitial lung disease on imaging. Renal involvement was around 7% in both sexes. 21.4% in M and 38.3% in F patients had gastrointestinal involvement. 92.9% of M and 55.9% in M patients had musculoskeletal involvement. Conclusions: We present the data on the first 74 patients with jSSc included in our cohort. Patients with male sex have a more severe disease similar to adult male patients. Disclosure of Interest: None declared